Calcium and vitamin D content in the menus offered to elderly people during spa treatment in Krynica-Zdrój resort - Jolanta Malinowska-Borowska; Anna Krzeszowska (Roczniki Panstwowego Zakladu Higieny, 2022)
Background. Calcium and Vitamin D are key nutrients in the diet of elderly people due to osteoporosis. One of the places where seniors, through observation, can gain knowledge on how to compose a meal to make it wholesome is a sanatorium that combines spa treatment and rehabilitation with diet therapy. Objective. The aim of the study was to assess the menus in terms of the content of calcium and vitamin D in the meals consumed by the elderly people during spa treatment in the health resort and to compare the results with the Polish Dietary Reference Values. Material and methods. The study was carried out at Krynica Zdrój resort among patients who underwent spa therapy as part of 14-day stay periods. Menus prepared for 3 different diets were assessed, namely regular diet, easy-to-digest diet and diet for diabetics with limitation of easily digestible carbohydrates. The meals were served for 309 people (194 women and 115 men) most of them aged over 50. Results. All meals served in the spa were deficient in calcium and vitamin D. The mean daily intake of calcium throughout the six months was 711.68 mg, whereas the Estimated Average Requirement (EAR) for both women and men is 1000 mg. The mean contents of vitamin D in all 3 served diets were at a similar level. The diets daily supplied approximately 4-5 μg vitamin D/person, which constituted about 30% of the daily requirement for this vitamin. Conclusions. In order to reduce the risk of diseases resulting from calcium and vitamin D deficiency, the amount of foods containing these nutrients should be increased in daily diet or, if this is impossible, they should be supplemented.